Determinant of purchase intention through online on halal cosmetic - Naseri, Roszi Naszariah Nasni (2023)
Globally, the rapid development of internet information technology has made e-commerce to become one of the main channels for people to shop online. This factor has changed the business model from the traditional distribution model (offline) into a new form of a business model (online) platform. In the case of Malaysia, the growth of the middle class and Muslims who were born in the digital era, has been the determining factors for online transactions. Due to this factor, the halal cosmetics industry has also witnessed a tremendous increase in consumer demands through online. However, due to the absence of physical interaction in the online environment, consumers purchase intention through online is declining because majority of Muslim consumers do not trust the online platform that sells halal cosmetics. As such, the current research attempt to investigate the purchase intention of Muslim customers towards purchase of halal cosmetics through online. Consequently, a self-administered questionnaire was used to collect data for the study from 400 Muslim consumers in Malaysia's central area. The data was examined using AMOS 22.0 SEM software and structural equation modelling. The findings of the study show that perceived ease of use, perceived usefulness, and attitude all influence the propensity to purchase halal cosmetics through online. The mediating effect of trust; and the moderating role of religiosity were also investigated. All the eight hypotheses evaluated in this study were confirmed to be significant and influence the purchase intentions of Muslim to purchase halal cosmetics through online. Also, the technology acceptance was found to leads to increase consumer purchase intention of halal cosmetics through online platform. The implication of the study is expected to aid the creation of a TAM model, specifically for online halal cosmetics consumer behaviour. This study also beneficial for halal cosmetics practitioners to make better and informed decision on halal cosmetics products through online platforms. In conclusion, the current study contributes to a better understanding of the important variables that influence consumers' purchase intention of halal cosmetics through online. This will assist the halal cosmetics industry to better advertise and position themselves in the competitive landscape and provide marketing practitioners a deep understanding of what leads consumers from various market segments to buy halal cosmetics through online.